The Antibacterial Activity of Liquid Soap supplemented with Extracts combination of Cyperus rotundus L. and Flowers of Plumeria acuminata, Michelia alba, or Cananga odorata Against Staphylococcus aureus and Escherichia coli Bacteria - Sri Mulyani; Ari Kusumawardani; Aulia Ageng Pangesti (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2022)
Secondary metabolites found in white Frangipani flowers (Plumeria acuminata), white tropical Magnolia flowers (Michelia alba), Ylang flower (Cananga Odorata), and Nutgrass (Cyperus rotundus L.) are thought to be employed as antibacterial active ingredients in detergent. This research aims to create liquid antibacterial soap using an extract mixture of Nutgrass with white Frangipani flower (F1), white tropical Magnolia flower (F2), or Ylang flower (F3). Phytochemical screening tests for the ethanol extracts of Nutgrass and those three flowers, pH tests, total active ingredients tests, and antibacterial activity tests against S. aureus and E. coli bacteria were carried out during the formulation of the liquid soap preparation with the addition of these extracts. The extraction procedure was maceration with a 70% ethanol solvent, yielding extracts of 9.28 percent frangipani flower, 8.12 percent white tropical Magnolia flowers, 9.8 percent Ylang flower, and 8.88 percent Nutgrass. The liquid soap quality testing findings met the established norms (SNI 4085:2017). This research shows that the soap formulas (F0, F1, F2, and F3) can inhibit S. aureus and E. coli germs in antibacterial activity tests using the disc diffusion method. Based on the diameter of the inhibition zone, the antibacterial activity against E. coli of liquid soap with Nutgrass & white tropical Magnolia flower extracts (F2) is not significantly different from liquid soap without extracts (F0). The F2 formula shows to be less effective than both the two liquid soaps containing extracts of Nutgrass & white Frangipani flower (F1) and Nutgrass & Ylang flower (F3). However, the three formulas of liquid soaps (F1, F2, and F3) tend to be more effective in antibacterial activity against S. aureus than a liquid soap that did not contain extracts (F0).